Addressing family members in Malay: a pilot study of young adults - Mansor, Nor Shahila; Hajek, John (2016)
Appropriate use of address is an important part of successful communication in all languages. In English the pronoun ‘you’ is the only form available in non-vocative address, e.g. ‘How are you?’ In Malay and Indonesian it is known that speakers not only have different forms of ‘you’ indicating relative formality, but also make frequent use of a range of nominal forms when directly addressing others, e.g ‘Ibu ke mana?’ (Where is mother going?/Where are you going?). While we already have some idea of the range of options and how they are used by speakers (e.g. Sneddon, Adelaar, Djenar and Ewing 2010), quantitative data and more fine-grained contextual detail are lacking. In this paper we report on the results of a pilot study which examined the use of address terms including ‘you’ directed by young adult speakers of Malay towards other family members. The data for this study were collected via questionnaire among 35 native speakers of Malay in Malaysia in 2015. All participants were students at Universiti Putra Malaysia and aged between 20-23 years old. The respondents were asked, amongst other things, in English to indicate the second person form of address they would use when addressing a range of interlocutors in a range of contexts. They were able to select from a range of options, i.e. Kin Terms (KN), Short Name (SN), Pronoun (Pr), Mixed Category (MC) and Full Name (FN) in the questionnaire. The Mixed Category refers to the combination of two forms of address, for instance KN+SN. In this study we present only the findings regarding the family domain considering the fact that “the sorts of social relations within the family are relatively clear, stable and well defined, when compared to other potential social relations and contexts” (Parkinson and Hajek, 2004: 100). The definition of family in this study is restricted to relations through blood (e,g, parents, sibling, cousin) or marriage (e.g. parents in-law). Our results show an overwhelming propensity for use of kin terms, as a sign of respect, when speaking to other relatives. Indeed this occurs without exception with older adults, such as parents and grandparents. However, while relative age and status are factors, gender plays no role. Within our respondents’ own generation, the treatment of cousins stands out: they are the only ones to be addressed with pronominal ‘you’ with any frequency. This pattern is unexpected – in other languages, no distinction is made in address towards siblings and cousins.